Joint decision-making and women’s agency on small-scale farms in Colombia and Nicaragua - García, Maria Alejandra; Godek, Wendy; Twyman, Jennifer (2021)
This research contributes to the gender and development literature that seeks to understand and measure women’s agency (or empowerment) through the study of intra-household decision-making. In this same vein, it provides insights to practitioners for monitoring and evaluating women’s empowerment or agency as critical outcomes of agricultural development programs. Conducting research on household decision-making with smallholder farm families is important for designing effective research and development interventions that foster gender transformative change. This study focuses on rural communities in two Latin American countries, Nicaragua and Colombia. We begin with a brief discussion of the recent literature on household decision-making. We continue with a description of the research methodology followed by a presentation of the findings. The article closes with a discussion of the findings and their implications for the methodologies used to assess women’s agency in agriculture in the realm of development programs in Latin America.